2012
DOI: 10.1007/s10103-012-1237-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural response of human corneal and scleral tissues to collagen cross-linking treatment with riboflavin and ultraviolet A light

Abstract: High success rates in clinical trials on keratoconic corneas suggest the possibility of efficient treatment against myopic progression. This study quantitatively investigated the in vitro ultrastructural effects of a photooxidative collagen cross-linking treatment with photosensitizer riboflavin and UVA light in human corneo-scleral collagen fibrils. A total of 30.8 × 2 mm corneo-scleral strips from donor tissue were sagittally dissected using a scalpel. The five analytic parameters namely fibril density, fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
2
26
1
4
Order By: Relevance
“…Additionally, these facts relativise a considerably contribution of living cells such as myofibroblasts to the elastic properties of scleral tissue (McBrien et al 2009) from rabbit eyes because all cells should be destroyed or might not exhibit any contractile capability after the freezing/thawing procedure. However, we neither observed disarrangement nor an increase of density and diameter of scleral stromal collagen as described in other studies (Jung et al 2011;Choi et al 2013) at applied low blue light intensities. We observed disorganization of collagen bundles and changes in fibril diameter as a sign of destruction only at higher blue light intensities (>200 mW cm À2 ).…”
Section: Storage Procedurescontrasting
confidence: 66%
“…Additionally, these facts relativise a considerably contribution of living cells such as myofibroblasts to the elastic properties of scleral tissue (McBrien et al 2009) from rabbit eyes because all cells should be destroyed or might not exhibit any contractile capability after the freezing/thawing procedure. However, we neither observed disarrangement nor an increase of density and diameter of scleral stromal collagen as described in other studies (Jung et al 2011;Choi et al 2013) at applied low blue light intensities. We observed disorganization of collagen bundles and changes in fibril diameter as a sign of destruction only at higher blue light intensities (>200 mW cm À2 ).…”
Section: Storage Procedurescontrasting
confidence: 66%
“…(D)) showed a clear irregular parallel arrangement of the collagen fibrils with tangled fibrils. Interestingly, the morphological changes were more pronounced in the short‐term group (BSS + DR + µF 7 , 7 days) than those in the long‐term group (BSS + DR 30 , 30 days), which was consistent with our previous reports (Jung et al ., ; Choi et al ., ,). Additionally, no significant difference in the changes in surface roughness was observed based on exposure condition.…”
Section: Resultsmentioning
confidence: 99%
“…The same conclusion has been reached by a number of previous studies, who demonstrated that cross-linking can increase the firmness of the scleral tissue. [22, 23] One of the most plausible mechanisms of collagen cross-linking in CXL is thought to be the creation of additional chemical bonds between histidine, hydroxyproline, hydroxylysine, tyrosine, and threonine amino-acid residues. [24] Note that CXL has been reported to have a certain impact on the biochemical properties of corneal tissue by increasing the resistance of corneal matrix against digestion by proteolytic enzymes such as pepsin, trypsin, and collagenase.…”
Section: Discussionmentioning
confidence: 99%
“…conducted an in-vitro study using riboflavin and UVA for CXL, and reported a significant increase in the density and area of collagen fibrils following CXL compared to non-cross-linked human scleras. [23] Furthermore, they found an increase in the scleral thickness and an irregular parallel arrangement of collagen fibrils with increased circumferences.…”
Section: Discussionmentioning
confidence: 99%